Mentoring pre-service educators in the development of professional disposition. Issue 3 (4th September 2017) - Kindall, Heather D.; Crowe, Tracey; Elsass, Angela
Abstract : Purpose: Professional dispositions must be cultivated through focused self-reflection and targeted, authentic, internship experiences prior to entering the teaching profession. Continued development through mentoring during the clinical internship can enhance the effectiveness of pre-service teacher candidates as instructional leaders. The purpose of this paper is to explore the unique experiences found to be successful in mentoring pre-service teachers from student to professional during an authentic, yearlong internship experience. Design/methodology/approach: Intern participants in this pilot study completed an inventory that measured professional dispositions five times during an internship experience. Data were analyzed using a mixed methods study design. Findings: Results of the study determined that intern participants held unrealistic views of teaching and did not recognize the importance of dispositional development prior to focused mentoring throughout the year of clinical internship. One central finding in this study is that change and growth about perceptions of professional dispositions can be developed through focused mentoring. Originality/value: Mentoring within the teacher preparation program can help in the transition of understanding professional growth and development, attitudes, and the view of complex behaviors. The dispositions necessary for effective teaching can be honed through cultural and clinical experiences, continual self-reflection, constructive feedback on evaluations of teaching, and targeted mentoring before beginning the clinical student internship and throughout the experience.